Modeling solar chromospheric spicules with intense lasers - Wang, Jianzhao; Zhong, Jiayong; An, Weiming; Zhou, Weimin; Wang, Chen; Zhang, Bo; Ping, Yongli; Sun, Wei; Yuan, Xiaoxia; Tang, Pengfei; Zhang, Yapeng; Zhang, Qian; et al. (Frontiers in Physics, 2023)
Solar spicules are small-scale jet-like structures in the lower solar atmosphere. Currently, the formation of these widely distributed structures lacks a complete explanation. It is still unclear whether they play an essential role in corona heating. Here, based on the magnetohydrodynamic scaling transformation relation, we perform experiments with the interaction of a high power laser with a one-dimensional sinusoidal modulated target to model solar spicules. We observe several spicule-like structures with alternating polarity magnetic fields around them.Magnetohydrodynamic simulations with similar parameters show the detail information during the spicules' formation. The results suggest that the so-called strong pulse model can lead to the formation of the solar spicules. The magnetic reconnection process may also play a part and lead to additional heating and brightening phenomena.